The effect of Salvia aroma on labor anxiety among primigravida and multigravida women: a randomized clinical trial - Forozan Sharifipour; Azam Bakhteh; Nader Salary (Tehran University of Medical Sciences, 2017)
Background & Aim: Mother's intense fear of and anxiety about labor pain lead to muscle contractions. Intense muscle contractions especially uterine contractions interfere with the normal process of labor. So, this study aimed to investigate the effect of salvia aroma on reducing the women's anxiety level during labor. Methods & Materials: The present study was a two-group randomized clinical trial (IRCT2016042727633N1) conducted in 2015 on 160 pregnant women laboring in Motazedi Hospital in Kermanshah. The subjects were randomly assigned into two groups. Prior to the intervention, the Spielberger's State-Trait Anxiety Inventory (STAI) was completed by both groups and the anxiety scores were determined. In the intervention group, immediately after the onset of the active phase of labor, a gauze impregnated with three drops of the salvia essence was attached to the samples' collars and repeated every half an hour. In the control group, a placebo was administered in a similar way. After the intervention, anxiety was measured at a cervical dilation of 5-7 cm. The chi-square test, Fisher test, Kolmogorov-Smirnov test, Wilcoxon and Mann-Whitney tests were employed to analyze the data. Results: The mean score for anxiety was similar in the two groups prior to the intervention (P=0.15). However, after the intervention the mean score for anxiety was lower in the aromatherapy group (39.86±10.39) than in the control group (64.25±7.41) (P<0.001). Conclusion: The findings suggested that the level of labor anxiety was reduced using aromatherapy with salvia essence. Accordingly, the use of salvia essence aroma is recommended for reducing anxiety labor.